2000
DOI: 10.1016/s0168-6445(00)00037-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate and energy-yielding metabolism in non-conventional yeasts

Abstract: Sugars are excellent carbon sources for all yeasts. Since a vast amount of information is available on the components of the pathways of sugar utilization in Saccharomyces cerevisiae it has been tacitly assumed that other yeasts use sugars in the same way. However, although the pathways of sugar utilization follow the same theme in all yeasts, important biochemical and genetic variations on it exist. Basically, in most non-conventional yeasts, in contrast to S. cerevisiae, respiration in the presence of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
0
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(156 citation statements)
references
References 187 publications
(226 reference statements)
6
141
0
9
Order By: Relevance
“…A more complete view, including compartmentation and other steps that occur in the mitochondria, may be found elsewhere (Flores et al, 2000). A futile cycle may occur during growth on C2 carbon sources.…”
Section: Resultsmentioning
confidence: 99%
“…A more complete view, including compartmentation and other steps that occur in the mitochondria, may be found elsewhere (Flores et al, 2000). A futile cycle may occur during growth on C2 carbon sources.…”
Section: Resultsmentioning
confidence: 99%
“…The glyoxylate cycle is an anaplerotic one, required for growth on carbon source of less than 3 carbon atoms (Flores et al 2000). A cytoplasmique aconitase converts citrate released out of the mitochondrion into isocitrate, then a cytosolic isocitrate lyase cleave isocitrate into succinate and glyoxylate.…”
Section: Glyoxylate Cycle and Isocitrate Lyasementioning
confidence: 99%
“…Furthermore, genetic engineering strategies to increase furan tolerance are likely to be proposed in the near future as Gorsich et al (2005) have demonstrated that deletion of the pentose-phosphate-pathway genes, ZWF1, GND1, RPE1 and TLK1, negatively affects furfural tolerance. Although NADPH, which is primarily generated via the pentose-phosphate pathway, is required for HMF reduction (Flores et al 2000;Wahlbom and Hahn-Hä gerdal 2002), furfural reduction has been linked to NADH (Wahlbom and Hahn-Hä gerdal 2002). However, it has been suggested that decreased NADPH generation reduces the overall reduction potential of the cell, thus leaving less NADH for furfural reduction .…”
Section: Improving Inhibitor Tolerance Of S Cerevisiaementioning
confidence: 99%